2020
DOI: 10.3390/en13174571
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Selection of Integrated Electricity Generation Systems for the Power Sector with Low Greenhouse Gas (GHG) Emissions

Abstract: : Cheap and clean energy demand is continuously increasing due to economic growth and industrialization. The energy sectors of several countries still employ fossil fuels for power production and there is a concern of associated emissions of greenhouse gases (GHG). On the other hand, environmental regulations are becoming more stringent, and resultant emissions need to be mitigated. Therefore, optimal energy policies considering economic resources and environmentally friendly pathways for electricity generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Their results showed that concentrated solar power (CSP) is still not an economically feasible solution for Pakistan. In another effort, Arif et al developed a comprehensive model to minimize the cost of electricity and emissions for the period 2018-2030 [8]. The model was based on multi-period mix integer programming (MPMIP) and solved by the General Algebraic Modeling System (GAMS), considering three scenarios of fuel switching, fuel balancing, and carbon capture and sequestration (CSS).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their results showed that concentrated solar power (CSP) is still not an economically feasible solution for Pakistan. In another effort, Arif et al developed a comprehensive model to minimize the cost of electricity and emissions for the period 2018-2030 [8]. The model was based on multi-period mix integer programming (MPMIP) and solved by the General Algebraic Modeling System (GAMS), considering three scenarios of fuel switching, fuel balancing, and carbon capture and sequestration (CSS).…”
Section: Literature Reviewmentioning
confidence: 99%
“…If the power plants are built near an energy Considering the carbon dioxide emissions, generation expansion planning (GEP) must consider the emissions produced by generating units [6]. To avoid environmental problems and ensure energy security, the future energy mix should include a greater proportion of renewable energy [7]. Maluku has abundant potential for renewable energy sources, such as hydropower, wind, solar, and biomass.…”
Section: Introductionmentioning
confidence: 99%
“…Oxides , (ZnO and Fe 2 O 3 ), hybrid oxides-amine, (CuO and MgO), metal–organic frameworks, and carbonaceous adsorbents , have been continuously used in carbon capture technology. One of the carbon storage methods is the hydrate composition used to emit CO 2 , that is, 1.2 mmol of CO 2 /g for H 2 O in the gas phase, using an agitator that moves the center of the tank to get more CO 2 hydrate formation at an operating condition of 80 bar and a temperature of 275 K.…”
Section: Introductionmentioning
confidence: 99%